2002
DOI: 10.1081/pln-120014070
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Labelled Organic Sulfur in Rhizosphere of Rape and Barley and in Non-Rhizosphere Soil

Abstract: Rape is known to require more sulfur (S) than is necessary for the secondary metabolite synthesis. It is hypothesized that its coarse root system harbors more homogenous microbial biomass specific for sulfur immobilization=remobilization. In a growth chamber experiment, this work examined the ability of rape and barley to take up the labile 35 S (including 35 S-SO 4 2À and 35 S-organic extracted by hot water). For that, the endogenous compounds of soil organic matter were previously labeled with 35 S-SO 4 2À f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The proportion of HW‐S related to immobilized S was substrate and soil dependent. In addition, our previous studies using calcareous arable soil sampled from the same experimental site, showed that plants requiring large amounts of S, such as rape and ryegrass, are able to deplete S from the HW‐S pool when the soil solution is sulphate‐S‐deficient (Vong et al , 2002, 2004, 2007). The results show that hot‐water extractable S is an active pool that is indicative of labile soil organic S readily available for plants.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of HW‐S related to immobilized S was substrate and soil dependent. In addition, our previous studies using calcareous arable soil sampled from the same experimental site, showed that plants requiring large amounts of S, such as rape and ryegrass, are able to deplete S from the HW‐S pool when the soil solution is sulphate‐S‐deficient (Vong et al , 2002, 2004, 2007). The results show that hot‐water extractable S is an active pool that is indicative of labile soil organic S readily available for plants.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently standard agricultural practice to fertilise Brassica crops with sulfur to enhance yield (reviewed in Walker and Booth, 2003), since even mild sulfur shortages can result in reduced yield and quality of Brassicaceae without the appearance of visible symptoms. Under natural conditions, the high amounts of sulfur required by Brassicaceae may be supplied by the complement of soil microorganisms associated with their roots, which oxidise elemental sulfur to sulfate, thiosulfate, and tetrathionate (Grayston and Germida, 1991;Vong et al, 2002). Of 273 bacterial isolates found in the rhizosphere of oilseed rape, 90 % were able to oxidise elemental sulfur (Grayston and Germida, 1991).…”
Section: The Effect Of Sulfur Nutrition On Plant Glucosinolate Contentmentioning
confidence: 99%
“…Of 273 bacterial isolates found in the rhizosphere of oilseed rape, 90 % were able to oxidise elemental sulfur (Grayston and Germida, 1991). After 35 S-labelled sulfate was applied to the rhizosphere, the roots of Brassica napus took up significantly more sulfate than did barley roots (Vong et al, 2002).…”
Section: The Effect Of Sulfur Nutrition On Plant Glucosinolate Contentmentioning
confidence: 99%
“…For instance, ammonium and sulphur were significantly more abundant in heat-treated samples compared to ‘native’ soils. Studies conducted with a modern barley variety revealed that an increased level of sulphate in the rhizosphere inhibits the rhizospheric arylsulfates activity [42], i.e., the enzyme catalysing the hydrolysis of sulphate esters into mineral forms available for plant uptake [43]. Conversely, a microbiota better adapted to nitrogen and sulphur metabolism, such as the one associated with the Desert genotype, may offset this mineral imbalance contributing to a more efficient plant sulphur uptake in the barley rhizosphere and, at least in part, to the observed growth phenotype.…”
Section: Discussionmentioning
confidence: 99%